Depatriarchalize institutions: challenge to achieve Gender equity and eradicating gender-based violence - Fernández Moreno, Sara Yaneth (Nomadías, 2024)
Several decades have passed since universities, especially public ones, in Colombia and Latin America revealed and named the Gender-based violence (GBV) that is generated and reproduced within Higher Education institutions (HEIs); the phenomenon that, more than sporadic, has shown to be structural in nature, only that it had been made invisible, normalized, and naturalized for years. This is the central theme of this text, which is a memory of what has happened precisely since the first research on the subject today; It presents a bold strategy, a decidedly feminist formulation, a necessary timeline, and an overview of the direction for people interested in the topic. The fabric displayed here is possible thanks to the National University Network for Gender Equality in Higher Education (RENUEGES) of Colombia and by the Institutional Action Plan for Gender Equality at the University of Antioquia (UdeA). It is a heartfelt and heartfelt text designed from feminist academic activism and reflective feminist action research.